ANALISIS FAKTOR YANG MEMPENGARUHI MAHASISWA BERWIRAUSAHA DI MASA PANDEMI COVID - Putri, Linzzy Pratami; Christiana, Irma (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2021)
Pandemics that occurred throughout the world, including Indonesia, resulted in all activities outside the home, such as studying in formal education, to be carried out at home. This causes boredom for students, including students. However, this causes students to have ideas for entrepreneurship from home. This study aims to see what factors influence student entrepreneurship during the Covid 19 Pandemic. The study population in this study were all students of the Faculty of Economics and Business UMSU with the sampling technique using accidental samples. The research method used is descriptive quantitative using factor analysis techniques. Where the results of the study state that there are only four dominant factors that affect employee performance during the Covid 19 pandemic, namely filling "free time", helping the economy itself, helping the family economy, and following trends.